E-016 In vitro vascular model material characterization. (22nd July 2019) - McCue, M; Merritt, W; Settanni, C; Becker, T
Abstract : Introduction: Endovascular devices aid in the treatment of heart failure, thrombus removal, and aneurysms. To assist in the testing and development of new endovascular devices, in vitro training models are used during the proof-of-concept and prototype testing phases of product development. Although current vessel-training models cast from human vasculature are anatomically accurate, the materials often used for casting (i.e. silicones and glass) do not accurately simulate the vascular compliance (modulus), wall friction effects (lubricity), and hardness values seen in native human vasculature. Thus, more flexible and comprehensive in vitro models are needed to better understand how endovascular devices (such as coils, stents, flow diverters, flow disruptors, liquid embolics, and thrombectomy devices delivered via guide catheters, guide wires, and delivery microcatheters) physically interact with the vessel wall and corresponding tissues. Methods: To address the shortcomings of commercially-available vascular flow models, materials were developed and optimized in this study to have similar mechanical properties to human tissue. To accomplish this, both donated 'fresh' cadaveric vascular tissues (common carotid artery) and synthetic biomimetic materials were mechanically characterized with a hybrid rheometer (DH-R 2, TA Instruments - Figure 1). Results: Via the rheometer, data was collected for luminal wall friction, radial compliance, shear modulus (G*), and elastic modulus (E*). Properties of cadaveric vessels and model materials were statistically compared, and the biomaterials were tuned to closely mimic the mechanical properties of the cadaveric vasculature. The biomaterials were manufactured into flow models. 3D printing manufacturing techniques were used to obtain repeatable anatomical accuracy. Validation of the models by partnered neurointerventionalists is underway to ensure realistic catheter trackability and anatomical accuracy. Discussion: The new biomimetic materials in this study were able to simulate the compliance and mechanical properties of human vasculature more closely than existing silicone, polyurethane, and glass models. The utilization of novel biomimetic materials within this in vitro vascular flow model will allow for more relevant benchtop testing of endovascular devices. These models have the potential to generate more accurate data on device performance and may reduce the need for costly in vivo studies. Disclosures: M. McCue: 1; C; Brain Aneurysm Foundation Grant-2018. W. Merritt: 1; C; Brain Aneurysm Foundation Grant-2018. 5; C; Northern Arizona University. C. Settanni: 1; C; Brain Aneurysm Foundation Grant-2018. 5; C; Northern Arizona University. T. Becker: 1; C; Brain Aneurysm Foundation Grant-2018. 5; C; Northern Arizona University, Aneuvas Technologies, Inc.